Financial Knowledge and Millennials Investing Behaviors in Indonesia - Aang Kunaifi; Ahnan Naufal Fadlil Akbar (JURNAL SOSIAL HUMANIORA (JSH), 2019)
This research aims to investigate investment behavior in Indonesia millennial generation. Three variables are used to explain millennial behavior to have an investment account or unit. Consistent multivariate result finds that financial knowledge is positively associated with investment behavior. The results are found personal factor such as age group and gender have relationship on investment behavior. Junior age group and female have more likely to have an investment account or unit.